Fractional erbium:YAG laser (2940 nm) plus topical hydroquinone compared to intradermal tranexamic acid plus topical hydroquinone for the treatment of refractory melasma: a randomized controlled trial. (4th July 2022) - Mokhtari, Fatemeh; Bahrami, Bahareh; Faghihi, Gita; Asilian, Ali; Iraji, Fariba
Abstract: Objectives: Melasma is a chronic acquired condition characterized by grayish-brown macules and patches with a distinct border on the face. Although various treatments methods have been suggested for treating melasma, none has been completely successful. The aim of the study was to compare the efficiency of erbium: yttrium–aluminum–garnet (Er:YAG) laser and 4% hydroquinone (HQ) with the effects of intradermal tranexamic acid (TA) and 4% HQ for the treatment of refractory melasma. Methods: The study included 31 female patients with refractory melasma. The left or right side of the patient's face was chosen randomly to receive laser therapy with topical HQ on the one side (i.e. the laser side) and intradermal injection of TA plus topical HQ on the other side (i.e. the mesotherapy side). Digital photography was performed at baseline, at the end of the treatment, and three months after the treatment as follow-up. Two independent dermatologists evaluated the modified Melasma Area and Severity Index (mMASI) score according to the pictures. Overall, 27 patients completed the study and went through the clinical evaluation. Results: Treatment using HQ in combination with either Er:YAG laser therapy or intradermal injection of TA significantly improved the hemi-mMASI and resulted in higher patient satisfaction. While the improvement was not significantly different between the two regiments after the treatment and upon follow up and both were equally efficient in the treatment of refractory melasma ( p  = 1.308), recurrence rate was higher after treatment with Er:YAG laser than TA (12% vs 34%). Conclusion: This study confirmed the comparable efficacy of TA plus topical HQ versus Er:YAG laser plus topical HQ for the treatment of refractory melasma. Both groups improved significantly and no subject left the treatment because of adverse effects. Trial registration number: IRCT20191011045057N1